Proyecto viable para la importación de pintura en polvo desde Brasil - Herrera Terán, Gina Paola (2014)
This plan is based on the need to establish a process for the importation of paint powder from Brazil to Ecuador, following a supply chain, based on appropriate processes and procedures to minimize the costs and times employees. Characteristics, uses and benefits of the powder coating, will analyze this will guarantee it the product required by the Ecuadorian market. Finally the recommendations and conclusions for the implementation of the import process will be to achieve the goals.